Comparison of the Luminal and Mucosa-Associated Microbiota in the Colon of Pigs with and without Swine Dysentery - Burrough, Eric R.; Arruda, Bailey L.; Plummer, Paul J. (Frontiers in Veterinary Science, 2017)
Colonic contents and mucosal scrapings from pigs inoculated with Brachyspira hyodysenteriae or Brachyspira hampsonii were collected at necropsy and classified as either positive (n=29) or negative (n=7) for swine dysentery based upon lesions and positive culture from the source pig. The microbiota in each sample was analyzed by bacterial census taking (16S rRNA gene sequencing). Procrustes analysis revealed similar clustering by disease classification with a relatively high M2 value (0.44) suggesting differences in the microbiota between mucosal and luminal samples from the same pig. In both sample types, differences in richness and beta diversity were observed between disease statuses (P ≤ 0.014). The relative abundance of Brachyspirales, Campylobacterales, Desulfovibrionales, and Enterobacteriales,was higher in pigs with dysentery for both mucosal scrapings and luminal samples while Clostridiales, Erysipelotrichales, and Fusobacteriales were significantly more abundant in the luminal contents only. For inoculated pigs that did not develop dysentery, Burkholderiales were more abundant in both sample types, Bacteroidales and Synergistales were more abundant in mucosal scrapings, and Lactobacillales and Bifidobacteriales were more abundant in luminal contents when compared with diseased pigs. Linear discriminant analysis of effect size revealed Brachyspira, Campylobacter, Mogibacterium, and multiple Desulfovibrio spp. as differential features in mucosal scrapings from pigs with dysentery while Lactobacillus and a Bifidobacterium sp. were differential in pigs without disease. These differential features were not observed in luminal samples. In summary, microbial profiles in both sample types differ significantly between disease states; however, evaluation of the mucosal microbiome specifically may be of higher value in elucidating bacterial mechanisms underlying development of swine dysentery.